Dysregulation of LXR responsive genes contribute to ichthyosis in trichothiodystrophy. Issue 3 (March 2020) - Hashimoto, Satoru; Takanari, Hiroki; Compe, Emmanuel; Egly, Jean-Marc
Highlights: The skin of Trichothiodystrophy (TTD) model mice showed abnormal lipid metabolism. Cholesterol dynamics was altered in keratinocytes derived from TTD mice when compared with WT. Expression of LXR responsive genes was abrogated both in TTD keratinocytes and in fibroblasts derived from TTD patients having ichthyosis. Abstract: Background: Trichothiodystrophy (TTD) is a rare autosomal recessive disorder characterised by brittle hairs and various systemic symptoms, including photosensitivity and ichthyosis. While photosensitivity could result from DNA repair defects, other TTD clinical features might be due to deficiencies in certain molecular processes. Objectives: The aim of this study was to understand the pathophysiological mechanism of ichthyosis in TTD, focused on the transcriptional dysregulation. Methods: TTD mouse skin tissue and keratinocytes were pathologically and physiologically examined to identify the alteration of lipid homeostasis in TTD with ichtyosis. Gene expression of certain lipid transporter was assessed in fibroblasts derived from TTD patients and TTD mouse keratinocytes. Results: Histopathology and electron microscopy revealed abnormal lipid composition in TTD mice skin. In addition to abnormal cholesterol dynamics, TTD mouse keratinocytes exhibit impaired expression of Liver X receptor (LXR) responsive genes, including Abca12, a key regulator of Harlequin ichthyosis, and Abcg1 that is involved in the cholesterol transport process in the epidermis. Strikingly, dysregulation of LXR responsive genes has been only observed in cells isolated from TTD patients who developed ichthyosis. Conclusions: Our results suggest that the altered expression of the LXR-responsive genes contribute to the pathophysiology of ichthyosis in TTD. These findings provide a new drug discovery target for TTD.